Credit Risk impact on Islamic Banks Listed in the Karachi Stock Exchange in Pakistan - Iqbal, Muhammad Saeed; Dr. Sofi Mohd Fikri, (Journal of Tourism, Hospitality, and Services Industries Research (JTHS), 2023)
This study examines the variables that impact the credit risk of Pakistani Islamic banks (IBs) in terms of credit quality. As such, this research requires a complete overview of credit risk factors and their effect on Pakistani Islamic banks' credit quality. In this study, all IBs registered on the Karachi Stock Exchange (KSE), which includes 10 IBs with data covering the years (2012-2022), have been included in the sample. Using the proportion of non-performing financing (NPF) to all Islamic bank financing, we can estimate credit risk. There are both Islamic bank-specific variables and macroeconomic variables that might contribute to credit risk in our study. Based on the findings of the multiple regression analysis, there appears to be a negative connection between the profitability, profit income, Islamic bank size, and Islamic bank type of each Islamic bank, as well as the amount of credit risk these IBs are exposed to in Pakistan. In addition, the results indicate that there may be a positive link between the level of credit risk in Pakistan's unemployment rate and banks' advanced credit quality. It is evident from the results, in any case, that banks' credit risk assessments do not appear to be significantly correlated with liquidity, growth, or gross domestic product. Islamic banks measure this. Overall, Islamic banks in Pakistan should take into account other factors besides liquidity, growth, and GDP when managing credit risk.